Development and validation of a nomogram for assessing risk of isolated high 2-hour plasma glucose - Sun, Kan; Xiao, Xianchao; You, Lili; Hong, Xiaosi; Lin, Diaozhu; Liu, Yujia; Huang, Chulin; Wang, Gang; Li, Feng; Sun, Chenglin; Chen, Chaogang; Lu, Jiahui; et al. (Frontiers in Endocrinology, 2022)
Objective: A tool was constructed to assess need of an oral glucose tolerance test (OGTT) in patients whose fasting plasma glucose (FPG) and hemoglobin A1c (HbA1c) are normal. Methods: Data was collected from the longitudinal REACTION study conducted from June to November 2011 (14,686 subjects, aged ≥40 y). In people without a prior history of diabetes, isolated 2-hour OGTT hyperglycemia was defined as 2-hour OGTT ≥ 11.1 mmol/L, FPG < 7.0 mmol/L, and HbA1c < 6.5%. A predictive nomogram for 2-hour OGTT hyperglycemia was developed via stepwise logistic regression. Discrimination and calibration of the nomogram were evaluated by the area under the receiver operating characteristic curve (AUC) and Hosmer-Lemeshow test; performance was externally validated in Northeast China. Results: Parameters in the model included gender, age, drinking status, marriage status, history of hypertension and hyperlipidemia, waist-to-hip ratio, FPG, and HbA1c. All variables were noninvasive, except FPG and HbA1c. The AUC of the nomogram for isolated 2-hour OGTT hyperglycemia was 0.752 (0.7717-0.787) in the development dataset. The AUCs of the internal and externally validation datasets were 0.781 (0.732-0.830) and 0.801 (0.776-0.827), respectively. Application of the nomogram during the validation study showed good calibration, and the decision curve analysis indicated that the nomogram was clinically useful. Conclusions: This practical nomogram model may be a reliable screening tool to detect isolated 2-hour OGTT hyperglycemia for individualized assessment in patients with normal FPG and HbA1c. It should simplify clinical practice, and help clinicians in decision-making.